(E)-Specific direct Julia-olefination of aryl alcohols without extra reducing agents promoted by bases1. Issue 36 (4th May 2015) - Yao, Chuan-Zhi; Li, Qiang-Qiang; Wang, Mei-Mei; Ning, Xiao-Shan; Kang, Yan-Biao
<x xml:space="preserve">Abstract</x> (E)-Specific direct Julia-olefination of aryl alcohols promoted by bases: a strategy of self-hydride transferring redox process.